2020
DOI: 10.3390/membranes10120415
|View full text |Cite
|
Sign up to set email alerts
|

Reducing the Impacts of Biofouling in RO Membrane Systems through In Situ Low Fluence Irradiation Employing UVC-LEDs

Abstract: Biofouling is a major concern for numerous reverse osmosis membrane systems. UV pretreatment of the feed stream showed promising results but is still not an established technology as it does not maintain a residual effect. By conducting accelerated biofouling experiments in this study, it was investigated whether low fluence UV in situ treatment of the feed using UVC light-emitting diodes (UVC-LEDs) has a lasting effect on the biofilm. The application of UVC-LEDs for biofouling control is a novel hybrid techno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 133 publications
(187 reference statements)
0
12
0
Order By: Relevance
“…Dhakal et al [39] developed and demonstrated the applicability of the flow cytometry (FCM)-based bacterial growth potential (BGP) method to assess the biofouling potential in seawater (SW) RO systems using a natural microbial consortium. Sperle et al [40] reported the potential of UVC irradiation using the recently developed UV-LEDs as an in situ pretreatment strategy for biofouling control in RO or NF systems. In contrast to UV studies carried out previously, they tested if low fluences are sufficient to not only delay the biofilm formation but further lead to a reduced hydraulic resistance of the biofilm while approaching a severe biofouling state.…”
Section: Conventional Thermal Technologiesmentioning
confidence: 99%
“…Dhakal et al [39] developed and demonstrated the applicability of the flow cytometry (FCM)-based bacterial growth potential (BGP) method to assess the biofouling potential in seawater (SW) RO systems using a natural microbial consortium. Sperle et al [40] reported the potential of UVC irradiation using the recently developed UV-LEDs as an in situ pretreatment strategy for biofouling control in RO or NF systems. In contrast to UV studies carried out previously, they tested if low fluences are sufficient to not only delay the biofilm formation but further lead to a reduced hydraulic resistance of the biofilm while approaching a severe biofouling state.…”
Section: Conventional Thermal Technologiesmentioning
confidence: 99%
“…For instance, LED lights are promising tools for in situ antimicrobial treatments along water distribution facilities such as plumbing installations and showerheads in order to prevent the development of opportunistic pathogens (Cates and Torkzadeh 2020 ). In addition, the installation of optical fibres within the plumbing network can provide a treatment solution for the internal surfaces of the pipes, as suggested by (Lanzarini-Lopes et al 2020 ), and also for reducing biofouling in membrane filtration systems (Sperle et al 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…drinking and wastewater disinfection. However, applying UV disinfection for other applications like using UV irradiation as pre-treatment for biofouling control in membrane filtration systems, , E. coli may not be the ideal model organism. Biofilms often consist of noninfectious, nonmodel organisms, which to our knowledge have not been used as challenge organisms, yet.…”
Section: Introductionmentioning
confidence: 99%
“…This study aims to provide a standardized biodosimetry protocol for flow-through reactors and to elucidate critical steps that mitigate artifacts exploring new UV treatment designs with bacterial cells (using LEDs or conventional lamps). This is achieved by comparing the existing methods for flow-through UV reactors and the subsequent evaluation of the most important steps resulting in a standardized and reproducible biodosimetry protocol for the nonmodel organism, Aquabacterium citratiphilum , a Gram-negative bacterium found typically in drinking water biofilms around Europe with potential relevance for biofouling of high-pressure membrane treatment …”
Section: Introductionmentioning
confidence: 99%